Implementation of the youth pledge in language month activities at Al-Irsyad High School, Banten and its influence on students - Naufal, Syahdan; Rofiroh, Rofiroh; Athfaliah, Khodikotul; Mumbasiroh, Siti; Fauziah, Siti Faza; Agustina, Reni Valen; Nazihah, Siti Nisrina; Wulandari, Dinda Esti (Journal of Community Service in Science and Engineering (JoCSE), 2025)
This study investigates how the values of the Youth Pledge are implemented through Language Month activities at Al-Irsyad High School, Banten, in 2024. The event incorporated various competitions including trilingual speech contests, storytelling, and chain poetry, aiming to enhance nationalism, language appreciation, and student character development. Employing a qualitative case study approach, data were collected through interviews, participatory observations, and documentation from students, teachers, and school administrators. Findings indicate that these activities significantly improve students' literacy, creativity, confidence, and sense of national identity. The integration of local culture and historical visits to Banten’s heritage sites further deepens the appreciation of cultural diversity and promotes character education. The study concludes that Language Month serves not only as a commemorative event but as a practical educational platform for embedding the spirit of nationalism among youth. Penelitian ini mengkaji bagaimana nilai-nilai Sumpah Pemuda diimplementasikan melalui kegiatan Bulan Bahasa di SMA Al-Irsyad, Banten, pada tahun 2024. Acara tersebut mencakup berbagai kompetisi termasuk lomba pidato trilingual, mendongeng, dan puisi berantai, yang bertujuan untuk meningkatkan nasionalisme, apresiasi bahasa, dan pengembangan karakter siswa. Dengan menggunakan pendekatan studi kasus kualitatif, data dikumpulkan melalui wawancara, observasi partisipatif, dan dokumentasi dari siswa, guru, dan administrator sekolah. Temuan menunjukkan bahwa kegiatan-kegiatan ini secara signifikan meningkatkan literasi, kreativitas, kepercayaan diri, dan rasa identitas nasional siswa. Integrasi budaya lokal dan kunjungan sejarah ke situs warisan Banten semakin memperdalam apresiasi keragaman budaya dan mempromosikan pendidikan karakter. Penelitian ini menyimpulkan bahwa Bulan Bahasa tidak hanya berfungsi sebagai acara peringatan tetapi juga sebagai platform pendidikan praktis untuk menanamkan semangat nasionalisme di kalangan pemuda.